Yuriy Drozd (dedicated to 75th Birthday) - Friends, The (Lugansk National Taras Shevchenko University, 2020)
On October 15, 2019 an outstanding Ukrainian mathematician, one of the founders of Kyiv algebraic school Yuriy Drozd celebrated his 75th birthday.